2017
DOI: 10.18001/trs.3.1.11
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Cigarette Expectancies in Smokers with Psychological Distress

Abstract: Objectives Very few studies have evaluated perceptions of electronic nicotine delivery systems (ENDS) among smokers with mental illness. This study assessed expectancies about the effects of smoking combustible cigarettes or using ENDS among current smokers with and without severe psychological distress (SPD). Methods We used a crowdsourcing system to survey 268 smokers on their expectancies for the effects of combustible cigarettes and ENDS. Positive expectancies assessed included negative affect reduction,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 34 publications
1
8
0
Order By: Relevance
“…For example, ENDS advertisements have claimed benefits including improved depression (74) and sociability (75). This could be one explanation for the recent finding that current smokers with SPD reported more positive expectancies that ENDS would improve social interactions (76). Moreover, never smokers with MHC could be especially attuned to these communications if they are curious about ENDS as a novel way to manage MHC symptoms, which could potentially explain disproportionate use of ENDS by never smokers.…”
Section: Discussionmentioning
confidence: 99%
“…For example, ENDS advertisements have claimed benefits including improved depression (74) and sociability (75). This could be one explanation for the recent finding that current smokers with SPD reported more positive expectancies that ENDS would improve social interactions (76). Moreover, never smokers with MHC could be especially attuned to these communications if they are curious about ENDS as a novel way to manage MHC symptoms, which could potentially explain disproportionate use of ENDS by never smokers.…”
Section: Discussionmentioning
confidence: 99%
“…Although little research has examined ENDS risk perceptions among people with MHC, a recent study found that only 34% of patients with schizophrenia considered e-cigarettes less harmful than traditional cigarettes [18]. Miller et al [22] found that although there were no differences in negative expectancies, smokers with severe psychological distress indicated more positive expectancies of ENDS (i.e., for positive social effects and weight control) than those without severe distress. It is possible that smokers with MHC are more optimistic about the potential benefits of ENDS than those without MHC.…”
Section: Introductionmentioning
confidence: 99%
“…In this study of adult AI who smoke, only a minority perceived that either smoking or vaping helps people to keep their weight down. In contrast, smoking and increasingly vaping are perceived as helping to keep weight down among many non-AI smokers in the U.S. [10, 2833]. In one US study, people who smoke perceived that cigarettes were better for weight control than were ECs [34].…”
Section: Discussionmentioning
confidence: 99%
“…In one US study, people who smoke perceived that cigarettes were better for weight control than were ECs [34]. Among non-AI smokers with psychological distress, ECs were perceived as having favorable effects on weight control, although less so than cigarettes [33]. In a study of young adults, weight concerns were associated with past 30 day EC use [32].…”
Section: Discussionmentioning
confidence: 99%